2020
DOI: 10.1177/0038038520904715
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Integration and Marginalisation: A Theoretical Model and an Empirical Study on Three Immigrant Groups

Abstract: Recent sociological discussions have examined the classic theme of social integration from the point of view of belonging and multiple solidarities. As a research topic, migration importantly elucidates these general sociological questions. Literature on migration, integration and transnationalism lacks an encompassing theoretical model, which limits our understanding of complex integration processes. We propose a multifocal model of migrant integration including three key foci of integration: the host society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Third, our results cannot be generalized to the general population or to other migrant populations. In an earlier study on working-age migrants in Finland, Russian-origin migrants were more transnationally oriented than the other 2 migrant groups-Somalis and Kurds-which is likely to manifest as a higher level of DIT use [44]. Notwithstanding these limitations, this study is an important contribution to the growing literature on health and DIT use in older adults.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Third, our results cannot be generalized to the general population or to other migrant populations. In an earlier study on working-age migrants in Finland, Russian-origin migrants were more transnationally oriented than the other 2 migrant groups-Somalis and Kurds-which is likely to manifest as a higher level of DIT use [44]. Notwithstanding these limitations, this study is an important contribution to the growing literature on health and DIT use in older adults.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Our study challenges and complements this approach by emphasizing the agency side of the phenomenon and asking how older adults with migration backgrounds also actively resolve issues related to their own health and well-being, for example, by using DIT and seeking healthcare abroad. This way, we depict the health service use of older migrants as an active process involving various geographical domains [ 18 ], and a complex interaction of virtual and real transnational spaces. Our results suggest that, although older adults with migrant backgrounds would be more likely to feel challenged in accessing THC compared to younger people, it is probable that they can overcome this challenge if they use DIT for multiple purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that low social integration in the destination country encouraged the utilization of THC. Kemppainen et al [ 18 ] showed that, among working-age migrants, the older age groups (55–64 years old) are less integrated into their destination societies than the younger age groups. Older migrants are exposed to specific conditions and risks of exclusion and social isolation [ 1 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Separation from one's primary family has been demonstrated to be significantly associated with the well-being and integration of migrants of Somali and Kurdish origin in Finland (Rask et al, 2016). Recent studies have drawn attention to multifocal marginalisation risk (T. Kemppainen et al, 2020) and the co-occurrence of substance use, affective symptoms and suicidal ideation (Salama et al, 2020) within the Kurdish migrant population in Finland.…”
Section: Three Migrant Groups In Finland: Backgroundmentioning
confidence: 99%